2013
DOI: 10.17851/2238-3824.18.2.89-104
|View full text |Cite
|
Sign up to set email alerts
|

Unidades fraseológicas com zoônimos: apresentação e localização em dicionários monolíngues e equivalentes de tradução em dicionários bilíngues

Abstract: Resumo: Este trabalho apresenta parte de uma pesquisa na qual se investiga, por um lado, a presença de unidades fraseológicas com zoônimos nos dicionários Houaiss e Borba e, por outro, seus equivalentes de tradução em dicionários bilíngues português-inglês/inglês-português. Os dicionários bilíngues escolhidos como fonte da pesquisa foram os que são encontrados com maior frequência entre os estudantes, e portanto os que têm acesso fácil. O objetivo da pesquisa é averiguar como as unidades fraseológicas com zoôn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…It is known that PUz are considered metaphorical expressions that integrate the culture of a people and their peculiar communication aspects, adding to them special 1 This article develops part of the doctoral research carried out and defended by this researcher (BUDNY, 2015). color and intimacy.…”
Section: Phraseological Units With Zoonyms In Bilingual School Dictiomentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that PUz are considered metaphorical expressions that integrate the culture of a people and their peculiar communication aspects, adding to them special 1 This article develops part of the doctoral research carried out and defended by this researcher (BUDNY, 2015). color and intimacy.…”
Section: Phraseological Units With Zoonyms In Bilingual School Dictiomentioning
confidence: 99%
“…The studies carried out by Budny (2015) on phraseological units with zoonyms demonstrated that some phraseologisms receive diversified equivalences in bilingual school dictionaries. Such fact may constitute an obstacle for these dictionary users, mainly if they are in classroom context, developing production activities where all of them are working in the same source-text, at the same time.…”
Section: The Nature and Variety Of Equivalences For Phraseological Unmentioning
confidence: 99%
“…Segundo Budny (2015), os coloquialismos zoonímicos ou unidades fraseológicas com zoônimos (UFz), como a autora as nomeia, são expressões metafóricas compostas de pelo menos um zoônimo e são integrantes da cultura de uma comunidade e/ou país. Esses coloquialismos expressam aspectos particulares da comunicação cotidiana.…”
Section: Introductionunclassified
“…Esse argumento justifica o estudo das expressões populares, como forma de facilitar a aprendizagem de uma língua estrangeira. Para embasar esse campo de estudos, são citados autores da área da Fraseologia e da Lexicografia como Xatara (1998), Ortiz Alvarez (2000), Budny (2015), entre outros. Como resultado, apresentamos uma amostra do levantamento bibliográfico, e análise de alguns correspondentes tradutórios, com tradução feita com base em pesquisas em dicionários e internet.…”
Section: Introductionunclassified
See 1 more Smart Citation